Fresno County Bar Association Law Day Luncheon with U.S. Attorney David Levy at Fresno Hilton Ballroom - Watkins, Howard::::::::: (1988)
U.S. Attorney David Levy giving his keynote address; Seated: Lawrence O'Neill